Factors Affecting Financing of Rural Agricultural Projects in Rwanda: Experience of Equity Bank (International Journal of Scientific Research and Management (IJSRM), 2021)
In the processes of financial deepening in low-income countries, lags prevail in the provision of services in the rural areas, particularly in the supply of the financial services required for agricultural activities and of those demanded by households that earn an important portion of their incomes from crops. This study examined factors affecting financing of rural agricultural projects in Rwanda with a focus on the experience of Equity Bank. Objectives were to assess how nature of existing financial products by Equity Bank influences financing of rural agricultural project in Rwanda; to examine how nature of rural agricultural projects in Rwanda influence access to Equity Bank’s financial services; to assess how characteristics of rural clients who engage in agricultural projects in Rwanda influence their ability to access Equity Bank’s financial services; and to examine influence of how rural agricultural environment in Rwanda influences ability of farmers to access Equity Bank’s financial services. Results revealed that there was a positive and significant relationship between factors influencing financial support and rural agricultural projects (rho=0.392, p value<0.05). Secondly, there was a positive significant relationship between financial services and farmers’ progress (rho =0.358, p value <0.05). Thirdly, there was a positive and significant relationship between farmers’ ability to access funds and rural agricultural projects (rho =0.562, p value <0.05). The research concluded equity bank to creates a strong coordination with rural farmers that indicated by the factor that the big number of respondents agree with the statements relate to successful projects. From on the shortcomings of the research, Equity bank is suggested to provide financial support whenever its necessary because a number of respondents disagreed with this statement and the rural agricultural projects leaders are suggested to rely most of the time on the financial institutions. Key words rural agricultural projects, Financing Factors